Titanium Dioxide - Material for a Sustainable Environment 2018
DOI: 10.5772/intechopen.72976
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Titanium Dioxide and Its Application for Photovoltaic Devices

Abstract: One-dimensional (1D) TiO 2 nanostructures (e.g., nanotubes, nanobelts, nanowires, and nanorods) have been considered to be very attractive candidates for various applications including photocatalytic degradation of pollutants, photocatalytic CO 2 reduction into energy fuels, water splitting, solar cells, supercapacitors, and lithium-ion batteries. More importantly, the dimensionality associated with zero-dimensional TiO 2 nanostructures gives unique physical properties, including a high aspect ratio structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Since their discovery, heterostructures of different dimensionalities have been increasingly used in photocatalytic applications [1][2][3]. Heterojunction nanostructured photocatalysts are now more appealing than individual elements because they have a synergistic effect that results in increased photocatalytic activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery, heterostructures of different dimensionalities have been increasingly used in photocatalytic applications [1][2][3]. Heterojunction nanostructured photocatalysts are now more appealing than individual elements because they have a synergistic effect that results in increased photocatalytic activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is a highly stable, nontoxic, inorganic, and inexpensive material, extensively studied in numerous morphological forms, e.g., films, nanoparticles, nanowires, nanotubes, and nanorods for a plethora of applications. One-dimensional (1D) nanostructures of TiO 2 provide an ideal platform for efficient solar vapor generation owing to their large surface area (high surface-to-volume ratio) and hydrophilic nature. However, such 1D nanomorphs have been rarely exploited for solar vapor generation due to their limited absorption across the entire solar spectrum, although there have been several attempts to simply increase light absorption using TiO 2 films with further treatments such as reduction and plasmonic effects. , …”
Section: Introductionmentioning
confidence: 99%
“…can be diverse by controlling certain parameters of growth, for example, the concentration of the electrolyte used and applied temperature conditions. 5,6 The crystallinity, grain size, and concentration of impurities have also been shown to influence the properties of the formed TNs. In recent years, mixed-phase TiO 2 nanostructures (MxPh-TNs) that impact the growth behavior of TiO 2 are most investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are certain studies that have reported that the growth behaviors of TNs (such as structure, composition, morphology, etc.) can be diverse by controlling certain parameters of growth, for example, the concentration of the electrolyte used and applied temperature conditions. , The crystallinity, grain size, and concentration of impurities have also been shown to influence the properties of the formed TNs …”
Section: Introductionmentioning
confidence: 99%